Central Bank Reaction Function for selected group of countries - Sun, Xiaoqing (Université d'Ottawa | University of Ottawa, 2005)
The topic covered in this paper is the performances of different reaction functions used as possible guidelines for the establishment of monetary policy. In exploring the nature of the reaction function, two alternative monetary policy rules have been con